Incentives in the Welfare State: Lessons for would-be welfare states - Assar Lindbeck (The Research Institute of Industrial Economics (IUI), 1996)
This paper deals with economic incentives and welfare-state arrangements in OECD countries. This paper emphasises what may be called 'dynamic' incentive issues, i.e. incentive effects that envolve over time. The discussion also covers the interplay between incentives and social norms among individuals, including endogenous changes in these norms.
Keywords: D60; D69; D71; 330; INCENTIVES; WELFARE STATE